Utilização de Quimiometria na avaliação da influência de diferentes níveis de circulação de ar na determinação de umidade por secagem em estufa de ar forçado - Catani, Natália Caroline (Universidade Federal de São Carlos, 2021)
Moisture content is one of the most relevant parameters for PepsiCo products, because its percentage could directly affect the quality and safety of the products. One of the main methods used to determine moisture in foods is drying it in an oven with forced air circulation. Equipment available on the market nowadays have settings which allows the control of air ventilation percentage, and air exchange with the environment. The official methods available are not updated at as quickly new equipment is released on the market, therefore the official methodologies presented some improve opportunities, because it hasn’t all necessary information about the parameters to perform analysis using new equipment. Using chemometric tools such as design of experiments and analysis of variance, it was possible to determine the importance and impact of the variables related to air ventilation in moisture content determination. Five models were proposed for main products, allowing the determination of the ideal configuration of oven settings for each product. This study had a big impact for the company, because its permitted the internal method update for three R&D laboratories in Latin America.
Use Of Chemometrics tools to evaluate the influence of different levels of air circulation on the determination of moisture by drying in forced air oven
Keywords: Planejamento fatorial; Alimentos; Análise de umidade; Umidade em alimentos; Design of experiments; Moisture content; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL